La Gestión Administrativa y la productividad laboral de los trabajadores y empleados de la dirección general de movilidad, tránsito y transporte del GAD municipal de Riobamba. - Jaramillo Pesántez, Mariuxi Lisette (2022)
This research determines the relationship and influence of administrative management on the productivity labor of workers and employees of the General Directorate of Mobility, transit and Transportation of the GAD of Riobamba city. For this purpose, the independent variable of administrative management is diagnosed according to its items, and its impact on the dependent variable, Labor Productivity. In addition, the degree of statistical relationship between both variables, their intensity and direction is calculated. Finally, strategies are suggested to improve administrative management in order to increase labor productivity. The statistical hypothesis that there is a relationship between administrative management and labor productivity is validated.